Immediate outcomes of bacterial meningitis in childhood may benefit from slow initial ββ-lactam infusion and oral paracetamol. (October 2011) - Taha, Muhamed-Kheir; Deghmane, Ala-Eddine
Evaluation of: Pelkonen T, Roine I, Cruzeiro ML, Pitkaranta A, Kataja M, Peltola H. Slow initial ββ-lactam infusion and oral paracetamol to treat childhood bacterial meningitis: a randomised, controlled trial. Lancet Infect. Dis. 11(8), 613–621 (2011). Acute bacterial meningitis is a medical emergency that requires prompt management. Despite effective antibiotic and adjunctive therapies, mortality is still unacceptably high in acute bacterial meningitis in children as this mortality did not substantially improve since the first use of antimicrobial therapies in the mid-20th century. ββ-lactams and particularly third-generation cephalosporins (ceftriaxone or cefotaxime) penetrate most body tissues and fluids, such as the cerebrospinal fluid, well. They are effective against the three most frequent bacterial causative agents of acute bacterial meningitis ( Neisseria meningitidis, Streptococcus pneumoniae and Hemophilus influenzae ). They are currently the consensual choices for the presumptive treatment of acute bacterial meningitis and usually used as a bolus every 4–6 h. Pelkonen et al. published a prospective, double-blind, single-center study with a two-by-two factorial design that aimed to explore the benefits in children of infused compared with bolus cefotaxime administration. Each group (bolus and infusion) was divided into two subgroups (with oral paracetamol or with placebo). No significant difference was observed for the final outcomes (mortality or severe neurological sequela and deafness) in the four subgroups. However, a post-hoc analysis of the results suggested that cefotaxime infusion plus paracetamol recipients had significant lower mortality during the first 72 h, irrespective of causative agents. However, the relevance of this study in sub-Saharan Africa is still difficult to evaluate as more than half of the initially assessed patients did not meet the inclusion criteria. The extension of the conclusions to developed countries may require further evaluations in terms of pharmacokinetic/pharmacodynamic properties as well as a thorough characterization of the causative agents under the view of the heterogeneous genetic structure of circulating bacterial strains in developed countries.